STRATEGIES TO CREATE AWARENESS AMONG COMMUNITY IN CASE OF MEDICAL EMERGENCIES - .M, Vignesh; .N. P, Muralidharan; Santhanam, Archana (International Journal of Psychosocial Rehabilitation, 2025)
The emergencies are unpredictable and non-assuming they are arising naturally while some are caused due to human activities and the need to evade and mitigate the seriousness of the risk is quite important and the successful strategies are to be carried out during medical catastrophe which causes devastating changes in human life and the emergency strategies of the country include the proper diagnosis of the population and the assigning and the availability of the certain emergency service numbers which helps to navigate and mitigate the prognosis of the disease and the improvement in technologies help to us to shield from the disease. A literature review was carried out from the scopuspubmed database. Aim of the study was to collect the successful strategies carried out by the government both in India and abroad. The first step for increasing awareness would be starting various advertisement campaigns. The next step would be implementing a unified emergency number (112 in India) to address all kinds of distress calls such as police, fire and ambulance. Awareness campaigns and training sessions for the general public should be conducted for the same, it is also necessary to spread awareness and help to populace know about the good samaritan law and even a short videos and catchy songs to demonstrate the seriousness of medical emergencies which is a great initiative by the government